Attention and salience in preference reversals - Carlos Alós-Ferrer; Alexander Ritschel (University of Zurich, Department of Economics, 2021)
We investigate the implications of Salience Theory for the classical preference reversal phenomenon, where monetary valuations contradict risky choices. It has been stated that one factor behind reversals is that monetary valuations of lotteries are inflated when elicited in isolation, and that they should be reduced if an alternative lottery is present and draws attention. We conducted two preregistered experiments, an online choice study (N = 256) and an eye-tracking study (N = 64), in which we investigated salience and attention in preference reversals, manipulating salience through the presence or absence of an alternative lottery during evaluations. We find that the alternative lottery draws attention, and that fixations on that lottery influence the evaluation of the target lottery as predicted by Salience Theory. The effect, however, is of a modest magnitude and fails to translate into an effect on preference reversal rates in either experiment. We also use transitions (eye movements) across outcomes of different lotteries to study attention on the states of the world underlying Salience Theory, but we find no evidence that larger salience results in more transitions.
Keywords: D01; D81; D87; 330; Preference reversals; eye-tracking; Salience Theory